1990
DOI: 10.1111/j.1442-9993.1990.tb01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection in the White‐plumed Honeyeater and the Fuscous Honeyeater at an area of sympatry

Abstract: Multivariate analysis on 15 habitat variables and quantitative data on foraging and interactive be/iaviour were used to Investigate habitat selection in the White-plumed Honeveater (Xichenostomus penicillatusj and the Euscous Honeyeater fLichenostomus fuscus^) at an area of sympatry in wood/and in New England Table/ands. Thirty-nine plots from four sites were used to examine significant differences in habitat uti/ization during the breeding period. The White-plumed Honeyeater associated strongly with narrow be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…They often forage in small flocks preferring middle and top parts of eucalypt trees. They aggressively defend preferred habitat from conspecifics (Chan 1990). Fuscous honeyeaters were shown to have low recapture rates (mean 1.4%, range 0-8.3% based on sites revisited after six months) and lacked genetic structure across 200 km in our study region, suggesting high mobility .…”
Section: Study Speciesmentioning
confidence: 71%
See 1 more Smart Citation
“…They often forage in small flocks preferring middle and top parts of eucalypt trees. They aggressively defend preferred habitat from conspecifics (Chan 1990). Fuscous honeyeaters were shown to have low recapture rates (mean 1.4%, range 0-8.3% based on sites revisited after six months) and lacked genetic structure across 200 km in our study region, suggesting high mobility .…”
Section: Study Speciesmentioning
confidence: 71%
“…Sites with greater numbers of large old eucalypts provide greater floral and nectar resources over longer flowering periods than sites where all such trees have been replaced with regrowth (Wilson andBennett 1999, Wilson 2003). Because fuscous honeyeaters prefer to feed on eucalypts (Chan 1990), sites with greater proportion of large old trees are expected to provide higher quality food resources for this species.…”
Section: Introductionmentioning
confidence: 99%
“…). In contrast to the other two honeyeaters that use mainly open dry forests and woodlands, the white‐plumed honeyeater is often associated with riverine habitat (Chan ), can adapt to urbanization (Higgins, Peter & Steele ) and is considered a ‘fragment specialist’ (Mac Nally & Horrocks ). All three honeyeaters typically exhibit biparental care, although instances of cooperative breeding have been reported (Higgins, Peter & Steele ).…”
Section: Methodsmentioning
confidence: 99%
“…The yellow-tufted honeyeater is considered to have the highest site fidelity of the three species, although specifics of movement patterns and dispersal distances are not well known for any of the three species (Higgins, Peter & Steele 2001;Amos et al 2012). In contrast to the other two honeyeaters that use mainly open dry forests and woodlands, the white-plumed honeyeater is often associated with riverine habitat (Chan 1990), can adapt to urbanization (Higgins, Peter & Steele 2001) and is considered a 'fragment specialist' (Mac Nally & Horrocks 2002). All three honeyeaters typically exhibit biparental care, although instances of cooperative breeding have been reported (Higgins, Peter & Steele 2001).…”
Section: Study Speciesmentioning
confidence: 99%
“…Many of these studies found that guild members often differ in their horizontal habitat selection and vertical foraging height (Cody 1968;Schoener 1974). For example, in Australia horizontal habitat differentiation was observed in treecreepers (Noske 1985), fantails (Cameron 1985), robins (Robinson 1992) and most often in honeyeaters (Recher 1971;Ford and Paton 1976;Chan 1990). Differences in foraging height were shown in Gerygones and thornbills (Recher 1989), and pardalotes (Woinarski 1985).…”
Section: Introductionmentioning
confidence: 99%